Biopolymer from marine Athelia and its application on heavy oil recovery in heterogeneous reservoir. (1st September 2018) - Xia, Wenjie; Dong, Xueqian; Zhang, Yonggang; Ma, Ting
Graphical abstract: A newly glucan biopolymers is synthesized with economically competitive cost, and shows the unique rheological properties and the excellent performance of profiling for heavy oil recovery. Highlights: Microbial polymer synthesized by newly Athelia strain. Biopolymer shows excellent properties of rheology even under extreme conditions. Optimization and cost estimation of production shows it more economic competition. Excellent performance on heavy oil recovery in high-temperature reservoir. Abstract: Biopolymer produced from marine Athelia strain presented unique Pseudoplastic behaviors under extremely-high temperature and salinity conditions. Characteristic analysis with FT-IR spectroscopy, high performance liquid chromatography, 1H and 13C NMR and two-dimensional COSY and HMQC spectra showed the structure of β-(1–6) glucans. Single-factor and orthogonal experiment design were used to optimize the yield, the maximum yield of the biopolymer was 28.32 g/L with 56.64% carbon conversion rate under optimized conditions. Economic investigation demonstrated that this novel biopolymer has great potential of commercialization with the competitive cost of $2896.04-5228.94 per ton for powder. Resistance factor and residual resistance factor were evaluated with core flooding experiments showed that this biopolymer had excellent performance of plugging capacity and profile modification, and indicating the great potential of application on heavy oil recovery.